Between-microcycle variability of external soccer training loads through the evaluation of a contemporary periodisation training model `CUPs` - Owen, A.; Weston, M.; Clancy, C. (International Journal of Sports Science & Coaching, 2024)
Objective Variation in training load is consistently demonstrated within weekly microcycles in soccer, yet less is known of load variations between the same weekday sessions across different microcycles. Our study aim was to examine between-microcycle variability in key measures of external training load.